The level of school anxiety and the specificity of its manifestations in children with down syndrome - Sukhonos , O. (Journal of Education, Health and Sport, 2023)
Children with Down syndrome studying in general schools together with children without this pathology often face an increased risk of maladjustment in the school environment. Due to the inadequacy of general education programs for children with developmental disabilities and the low level of awareness of school teachers and, especially, neurotypical school-age children about effective strategies for interacting with children with Down syndrome, the latter have an increased risk of developing school anxiety. The aim of the study was to determine the level of school anxiety depending on the ability to verbal communication in children with Down syndrome. Materials and methods: The research was carried out on the basis of the National Medical Center of ZOR, 97 children with Down's syndrome were thoroughly examined. The patients were divided into two groups according to the criterion of the ability to verbal communication: group 1 (G1) included 77 children capable of verbal communication, group 2 (G2) - 20 children who do not speak. Results of the study. As a result of the research, the level of school anxiety in its various aspects was established, depending on the ability to verbal communication in children with Down syndrome. Children with Down syndrome who are able to communicate were found to have significantly higher anxiety scores on almost all subscales than children with Down syndrome who are not able to communicate verbally. In children with Down syndrome who are incapable of verbal communication, a pathological decrease in anxiety in its various aspects is much more often noted, which may indicate a lack of understanding of social situations as a result of the lack of sufficient experience of being in a team (due to the inability to verbally produce the quality and quantity of communicative practices in such children suffer significantly). Children with Down syndrome who are able to talk have shown pathological reductions in school anxiety only in rare cases.